Governance and Service Delivery: Practical Applications of Social Accountability Across Sectors - and Wetterberg, Anna; Brinkerhoff, Derick W.; Hertz, Jana C. (RTI Press, 2016)
The six case studies in Governance and Service Delivery: Practical Applications of Social Accountability Across Sectors illustrate the multiple ways citizen participation in accountability – called social accountability – can lead to positive effects on governance, citizen empowerment, and service delivery. Drawing on their extensive experience implementing international donor-funded programs and projects, the authors examine six recent RTI International projects in Africa and Asia. The analysis focuses on both intended and actual effects, and it unpacks the influence of context on implementation and outcomes achieved, as well as on prospects for sustainability. Donors, academics, policy makers, practitioners and others interested in sustainable development and governance will find this systematic review invaluable.